Українська підляська говірка в поезії Юстини Королько: морфологічний рівень - Яворський, Андрій Юрійович; Yavorskiy, Andriy (Східноєвропейський національний університет, 2013)
У творах поетеси з Північного Підляшшя (Польща) Юстини Королько проаналізовано особливості підляської говірки на морфологічному рівні, зокрема простежено специфіку формотворення іменників, прикметників, дієслів, відмінності у структурі та відмінюванні займенників, спорадично в оформленні числівників і прислівників. З’ясовано специфіку використання авторкою діалектних елементів. Peculiarities of Podlasie dialects on morphological level, including specificity of nouns, adjectives and verbs form-building, differences in pronoun structure and conjugation, in numerals and adverbs processing are fully and systematically reflected in the works of Ukrainian poet from the North Podlasie (Poland) Justine Korolko. The dialectal inflection phenomena allowed to qualify the dialect used in the texts as  an archaic North Ukrainian. J. Korolko not only attempted to use certain dialect elements or imitation of dialect speech. Her works are written in Podlasie dialect, which essentially serves as a literary language. The texts fully represent the North Podlasie Ukrainian dialects and can be successfully used as a material for dialectological studies.
Ukrainian Podlasie Dialect in Justine Korolko’s Poetry: Morphological Level
Keywords: підляські говірки; словозміна; архаїзм; інновація; граматична аналогія; Podlasie dialects; inflections; archaism; innovation; grammatical analogy